NTA and FRCN Pedophilia Programmes in South- East Nigeria: An Evaluative Study - Chioma Rose Chime-Nganya; Nwoga Chibuzor Cosmas; Chukwuemeka Ononuju Nwankiti; Obin Ogban Obin; Sanita Ekwutosi Nwakpu (Budapest International Research and Critics University, 2024)
This study investigated the influence of NTA and FRCN pedophilia messages on residents of South-East Nigeria. The study has two objectives and one theoretical framework. It used survey research method in which 384 respondents were reached with a structured questionnaire out of which 375 valid responses were obtained. The data were analysed using descriptive statistics and Chi-Square tests using SPSS 20. The study ascertained that residents of Southeast, Nigeria got exposed to NTA & FRCN pedophilia programmes majorly through jingles, phone-in programmes and documentaries. The study also established that residents of Southeast, Nigeria, were aware of their responsibilities towards eradicating the menace of pedophilia in the society and were willing to take positive sections in that direction, as their exposure to broadcast media programmes on the subject of pedophilia increased their motivation to report cases of such to the appropriate authorities. The study recommended that media houses in South-East, Nigeria, should maintain their advocacy of child rights protection as well as call on public figures to get more involved by instituting formal or informal campaigns against pedophilia, among others.